About communication in social media – an analysis of the Polish PresidencyFacebook Profile from a perspective of social communication theory - TOMICZEK, MARTYNA (Journal of Education Culture and Society, 2020)
The half year of the Polish Presidency on the one hand was a great challenge but from the other hand a tremendous chance to promote the country and society. Activities were taken up in many different areas – using new technologies was an important part of the project, including new media which by the creation of the Polish Presidency FacebookProfi leturned out to be an integral part of Presidency. Using the possibility of providing a two–way communication proved that the potential of Facebook was understood. Running the fan page also showed a new face of diplomacy putting it in the area of public diplomacy.